KEBIJAKAN PENDIDIKAN KEJURUAN DI KOTA TERNATE DALAM KONTEKS MASYARAKAT EKONOMI ASEAN - Habsyi, Irsan; Arifin, Bustanul (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2024)
This research talks about vocational education policy in the city of Ternate in the context of the ASEAN economic community, and the type of research is qualitative to find an observation of a weakness or naturalistic aspect of an event, exploring the problem phenomologically. The form of in-depth, unstructured interviews through suggestions from those who examine the authentic lives or “life worlds” of the perpetrators. That observation data must be in-depth and detailed, the data must be depicted clearly, the description is sufficient so that the reader can understand what happened and how it happened. The research location is at a vocational school in the city of Ternate, in this case the researcher tries to research the preparation of students in facing the global market in the work sector and currently what is happening regarding ASEAN issues and research results is that vocational schools in the city of Ternate have prepared themselves for global competition and are preparing skilled workers who are ready to be used in the world of work.